TIME-SHIFTED CONDITIONAL ACCESS - KAMPERMAN, FRANCISCUS, LUCAS, ANTONIUS, JOHANNES (2003)
In a conditional access system, transmitted information is recorded in a scrambled form SV. Accordingly, any access to the recorded information SV is subject to the condition that proper control word(s) CW are available. To enable access to the recorded information SV, control word regeneration data ECM, KRD is stored. The proper control word(s) CW cannot easily be derived from this control word regeneration data ECM, KRD. However security device SCD is capable of retrieving the proper control word(s) CW from the control word regeneration data ECM, KRD. A system operator effectively masters operations carried out in the security device SCD. Accordingly, if the system operator so desires, he may inhibit retrieval of the control word(s) CW and, consequently, prevent access to the recorded information SV. The conditional access system may be used in, for example, pay-TV or multimedia purposes.